2020
DOI: 10.3390/molecules25030724
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin, an Active Constituent of Turmeric Spice: Implication in the Prevention of Lung Injury Induced by Benzo(a) Pyrene (BaP) in Rats

Abstract: Benzo(a)pyrene (BaP) is a well-known carcinogen and enhances oxidative stress and apoptosis and also alters several molecular pathways. Curcumin is an active ingredient of Curcuma longa, and it has potent anti-inflammatory, antioxidant activity that defends cells from oxidative stress and cell death. The objectives of the present study were to explore the protective effects of curcumin against long-term administration of BaP induced disturbances in lungs of rats. Male rats were randomly divided into four group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 46 publications
(55 reference statements)
0
29
0
Order By: Relevance
“…Regulations of coronavirus-infection-associated responses by curcumin is also suggested ( Chen et al, 2020 ). Moreover, curcumin has been shown to modulate various pathophysiological consequences of SARS-CoV-2 infection ( Akinyemi et al, 2015 ; Almatroodi et al, 2020 ; Dai et al, 2018 ; Hongtao et al, 2018 ; Kunnumakkara et al, 2017 ; Pang et al, 2015 ; Praditya et al, 2019 ; Titto et al, 2020 ; Vishvakarma, 2014 ). Nevertheless, the entry of SARS-CoV-2 into host cells is also predicted to be hindered by curcumin through direct interaction with viral ligands/target cell receptors ( Kandeel and Al-Nazawi, 2020 ; Maurya et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regulations of coronavirus-infection-associated responses by curcumin is also suggested ( Chen et al, 2020 ). Moreover, curcumin has been shown to modulate various pathophysiological consequences of SARS-CoV-2 infection ( Akinyemi et al, 2015 ; Almatroodi et al, 2020 ; Dai et al, 2018 ; Hongtao et al, 2018 ; Kunnumakkara et al, 2017 ; Pang et al, 2015 ; Praditya et al, 2019 ; Titto et al, 2020 ; Vishvakarma, 2014 ). Nevertheless, the entry of SARS-CoV-2 into host cells is also predicted to be hindered by curcumin through direct interaction with viral ligands/target cell receptors ( Kandeel and Al-Nazawi, 2020 ; Maurya et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Histological observation of lungs indicated that supplementation with HJE or NHJE at a high dose (1.5 g/kg BW) attenuated B(a)P-induced lung injury ( Figure 3 C). In addition, H&E-stained lung tissue sections displayed that B(a)P treatment caused disruption of lung architecture [ 36 , 37 , 38 ], including poor arrangement of epithelial cells lining bronchiole and abnormal morphology of alveolar structure (inflated alveolar sacs and thickened or ruptured interalveolar septa). However, the severity of B(a)P-induced histological damage in the lungs was reduced in mice supplemented with HJE or NHJE-H ( Figure 3 D).…”
Section: Resultsmentioning
confidence: 99%
“…Curcumin is capable of suppressing the production of reactive oxygen species (ROS) and this capability results from conjugated double bonds (Chikara et al, 2018). The extensive application of curcumin is because of its excellent pharmacological activities including antioxidant (Almatroodi et al, 2020; Mirzaei et al, 2018), anti‐inflammatory (J. Xu, Jia, Chen, & Wang, 2020), antitumor (Hesari et al, 2019; Salehi et al, 2020; Shabaninejad et al, 2020), neuroprotective (J. Wang, 2020), antimicrobial (Pourhajibagher, Partoazar, Alaeddini, Etemad‐Moghadam, & Bahador, 2020), lipid‐modifier (Zhai et al, 2020), antianalgesic (Bulboaca, Bolboaca, Stanescu, Sfrangeu, & Bulboaca, 2017), hepatoprotective (Y. Lu, Wu, Xiang, Li, & Lin, 2020), cardioprotective (Ahmed, Khan, & Mirzaei, 2019; Y. Chen et al, 2020; Hallajzadeh et al, 2019), and osteoprotective (C. Yang et al, 2020). Curcumin has demonstrated great efficacy in the treatment of nonalcoholic fatty liver disease (NAFLD).…”
Section: Pharmacological Profile Of Curcuminmentioning
confidence: 99%